PENGARUH QUALITY OF WORK LIFE, BUDAYA ORGANISASI DAN MOTIVASI KERJA TERHADAP KINERJA GURU SMA SWASTA DI KECAMATAN SERPONG, TANGERANG SELATAN - Siti Nurdianah; Saiful Anwar; Ichwani Siti Utami (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Teacher performance is a key determinant of educational quality and is influenced by various organizational and individual factors. However, improving teacher performance remains a challenge due to issues related to work environment, organizational culture, and work motivation. This study aimed to examine the effects of Quality of Work Life, organizational culture, and work motivation on the performance of teachers at private senior high schools in Serpong District, South Tangerang. The research employed a quantitative approach using a survey method. The population consisted of 220 teachers, while 142 teachers were selected as research samples using proportionate random sampling based on the Slovin formula. Data were collected through a structured questionnaire using a five-point Likert scale. Prior to hypothesis testing, the instrument was tested for validity and reliability, followed by classical assumption tests, including normality, linearity, multicollinearity, and heteroscedasticity tests. Data were analyzed using descriptive statistics, multiple linear regression, t-test, F-test, and the coefficient of determination with the assistance of IBM SPSS Statistics version 26. The findings revealed that Quality of Work Life, organizational culture, and work motivation each had a positive and significant effect on teacher performance. Simultaneously, these three independent variables also demonstrated a positive and significant influence on teacher performance, indicating that improvements in teachers' quality of work life, organizational culture, and work motivation contribute substantially to enhancing teacher performance. These findings provide empirical evidence for school management in formulating policies to improve teacher performance and educational quality.